VSL#3 probiotic treatment decreases bacterial translocation in rats with carbon tetrachloride‐induced cirrhosis. (12th May 2014) - Sánchez, Elisabet; Nieto, Juan C.; Boullosa, Ana; Vidal, Silvia; Sancho, Francesc J.; Rossi, Giacomo; Sancho‐Bru, Pau; Oms, Rosa; Mirelis, Beatriz; Juárez, Cándido; Guarner, Carlos; Soriano, Germán
Abstract Background & Aims Probiotics can prevent pathological bacterial translocation in cirrhosis by modulating intestinal microbiota and improving gut barrier and immune disturbances. To evaluate the effect of probiotic VSL#3 on bacterial translocation, intestinal microbiota, gut barrier and inflammatory response in rats with experimental cirrhosis. Methods Forty‐six Sprague‐Dawley rats with CCl4‐induced cirrhosis were randomized into two groups: VSL#3 group (n = 22) that received VSL#3 in drinking water, and water group (n = 24) that received water only. Treatment began at week 6 of cirrhosis induction and continued until laparotomy, performed 1 week after development of ascites or at week 20. A control group included 11 healthy rats. At this study end, we evaluated bacterial translocation, intestinal flora, intestinal barrier (ileal claudin‐2 and 4, β‐defensin‐1, occludin and malondialdehyde as index of oxidative damage) and serum cytokines. Results Mortality during this study was similar in the VSL#3 group (10/22, 45%) and the water group (10/24, 42%) (P = 1). The incidence of bacterial translocation was 1/12 (8%) in the VSL#3 group, 7/14 (50%) in the water group (P = 0.03 vs. VSL#3 group) and 0/11 in the control group (P = 0.008 vs. water group). The concentration of ileal and caecal enterobacteria and enterococci was similar in the two groups of cirrhotic rats. The ileal occludin concentration was higher and ileal malondialdehyde and serum levels of TNF‐α were lower in the VSL#3 group than in the water group (P < 0.05). Conclusions VSL#3 decreases bacterial translocation, the pro‐inflammatory state and ileal oxidative damage and increases ileal occludin expression in rats with experimental cirrhosis.